99mTc-Labelled Cu(I)-EHDP, a Potential Skeletal Imaging Agent - Agha, N.H.; Al-Hilli, A.M.; Hassen, H.A. (Nuklearmedizin - NuclearMedicine, 1981)
99mTc-Cu-EHDP has been prepared with high labelling yield applying for the first time the method of instantly formed cuprous ions in the mixture. A gelchromatography column scanning technique has been used to study the 99mTc fractions in the preparation. The study of the influence of pH-value on the amount of 99mTc-Cu-EHDP fraction shows that pH 1.6 - 1.7 gave the best labelling results. The formation rate of 99mTc-Cu-EHDP complex with a high labelling yield was fast and achieved within a few mins. This suggests the reduction of 99mTc-pertechnetate to Tc (IV). The final preparation was found stable for at least 4 hrs after mixing the reactants with the 99mTc-eluate. Comparative biokinetic studies of 99mTc-Cu-EHDP and 99mTc-Sn-EHDP in rabbits and mice showed a high bone uptake and fast elimination of 99mTc-Cu-EHDP from the skeleton. No significant difference was found in the plasma protein binding of 99mTc-Cu-EHDP and 99mTc-Sn-EHDP in rats as assessed by the GCS-technique. Radionuclide imaging in rabbits, using a gamma camera, showed 99mTc-Cu-EHDP to be a good bone-imaging agent.